PROBLEMS IN THE CIRCULATORY SYSTEM IN ADOLESCENTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article explores the prevalent issues affecting the circulatory system in adolescents, focusing on their causes, prevalence, and potential interventions. Through a comprehensive literature review and analysis of recent studies, it identifies key risk factors, diagnostic methods, and management strategies. The study aims to provide insights for healthcare professionals and policymakers to address these health challenges effectively.